2005
DOI: 10.1016/j.surfcoat.2004.08.154
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural, mechanical, and corrosion characterization of plasma-nitrided plastic injection mould steel

Abstract: Plasma nitriding can be used to improve wear and corrosion behaviour of moulds for plastic injection by modifying the near-surface layers of these materials. In this study, a ferritic stainless steel (X36CrMo17) was plasma nitrided at 520-540 8C for 15-18 h under various gas mixtures of N 2 +H 2 in an industrial nitriding facility. The nitrided layer microstructures, thicknesses, and strengths were studied by X-ray diffraction (XRD), conversion electron and X-ray Mfssbauer spectroscopies (CEMS and CXMS), cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…The plastic injection moulding industry is one of the fastest-growing industries in the world since a lot of products that are used in daily life involve the use of plastics [27][28][29]. Despite having numerous advantages, namely high dimensional and geometric precision, repeatability, and adaptability to a wide range of raw materials [30,31], the costs associated with the mould and the injection machine are high [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The plastic injection moulding industry is one of the fastest-growing industries in the world since a lot of products that are used in daily life involve the use of plastics [27][28][29]. Despite having numerous advantages, namely high dimensional and geometric precision, repeatability, and adaptability to a wide range of raw materials [30,31], the costs associated with the mould and the injection machine are high [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that acids and chlorides formed due to the decomposition of thermoplastics by overheating can create a corrosive environment [1]. Furthermore, during the injection moulding process, liberated gases from plastic materials at elevated temperatures can cause localized corrosion on the mould material [15]. On the other hand, plastic injection moulds suffer mechanical wear due to the relative movements of the mould parts, as well as due to the abrasive actions exerted by the reinforcement materials such as hard and abrasive fibres or whiskers [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In this investigation realized by Ozturk et al [15] a ferritic stainless steel (X36CrMo17) was plasma nitrided at 52-540…”
Section: Introductionmentioning
confidence: 99%